MEKANISME KEGAGALAN PAHAT PADA PROSES MILLING AKIBAT ALIRAN SERPIHAN PEMESINAN KECEPATAN TINGGI AISI 4140 - Saputra, Aswin; Yunus, Surya Murni (MEKANIK: Jurnal Ilmiah Teknik Mesin, 2017)
The mechanism of tool failure is the way to wear wear damage on the tool. This study aims to investigate the mechanism of tool wear / tool wear (Vb) which is useful to provide information on the wear mechanism of the tool in a high-speed, dry machining process with a HSS Cobalt M42 tool used for machining milling of AISI 4140 steel material. the cutting speed (v) differs above 200 m / min, the cutting depth (a) = 0.5 mm, the feeding motion (f) = 0.5 mm / min and the main cutting angle of the tool (Kr) = 90 ° at the rate condition high speed cutting. From the results of the study the mechanism of tool failure that occurs is side wear. Where the highest wear wear occurs in conditions v = 755 m / min, f = 0.5 mm / min, a = 0.5 mm, with flake thickness (hc) = 0.88 mm and flake flow velocity (Vc) = 431.42 m / where the value of Vb = 0.325 mm. The wear mechanism that occurs due to the flow of debris that moves upward touches the cutting edge of the tool with the shape of the broken debris.